2017
DOI: 10.1080/13554794.2017.1334802
|View full text |Cite
|
Sign up to set email alerts
|

A neuropsychological study of older adult first-time sex offenders

Abstract: Older adult sex offenders, overall, demonstrated poorer neuropsychological performance than older adult non-sex offenders did, although there was no difference between older first-time and historical offenders. Cognitive deficits may increase the risk of sexual offending due to impaired capacity in self-regulation, planning, judgment, and inhibition. A proportion of older adult sex offenders may be harboring acquired frontal lobe pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 77 publications
1
23
0
Order By: Relevance
“…Studies that described arguments for "pragmatic reasons" outlined the issue of small numbers of possible participants (Washington, 1989;Sodhi-Berry et al, 2015;Barry et al, 2014;Rodriguez et al, 2017;Coid et al, 2002) and for these reasons chose lower cut-offs, which allowed them to assure statistical power (Sodhi-Berry et al, 2015).…”
Section: Rationales For Choosing Age Cut-offsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies that described arguments for "pragmatic reasons" outlined the issue of small numbers of possible participants (Washington, 1989;Sodhi-Berry et al, 2015;Barry et al, 2014;Rodriguez et al, 2017;Coid et al, 2002) and for these reasons chose lower cut-offs, which allowed them to assure statistical power (Sodhi-Berry et al, 2015).…”
Section: Rationales For Choosing Age Cut-offsmentioning
confidence: 99%
“…The category "other" was used for the following: one study provided an average age only (Aday, 1994) and one study based their age cut-off on clinical experience of one author (McLeod et al, 2008). Rodriguez et al (2017) conducted a neuropsychological study and based their cut-off decision on findings of age-related changes in "cognitive functioning".…”
Section: Rationales For Choosing Age Cut-offsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, despite being a systematic review paper, the overall sample considered in the paper is very small (26 individuals). Rodriguez et al (2017) sample of first time and historic older sex offenders demonstrated poorer neuropsychological performance than older non-sex offenders did, although there was no difference between the older first-time and historical offenders. Cognitive deficits may increase the risk of sexual offending because of impaired capacity in self-regulation, planning, judgment and inhibition.…”
Section: Sex Offendersmentioning
confidence: 69%